Risk assessment industry driven approach in occupational health and safety - Hollá, Katarína; Kuricová, Alena; Kočkár, Samuel; Prievozník, Pavol; Dostál, Filip (Frontiers in Public Health, 2024)
Risk assessment and management in companies plays a significant role in the prevention section of any field. In the field of Occupational Health and Safety (OHS), its inconsistent or incorrect application has a direct impact on the life and health of employees. In some companies, even today, it is not properly implemented and adequate procedures and methods are not used. The article discusses the development of a step-by-step procedure for risk assessment in industrial environments in the area of OHS. Main parts of the model and its steps present the partial results of a survey conducted on a sample of 500 small and micro enterprises in the field of risk assessment and the systematic procedure developed following the main survey results. The survey covered only enterprises located in the construction, manufacturing, transport and storage and agriculture, forestry and fishing sectors, which is also a significant statistical feature. Within the structure of respondents, statistical features such as: size of enterprise, sector, region by work are identified. Only enterprises with size by number of employees -micro enterprises from 1 to 9 employees and small enterprises from 10 to 49 employees -were included for the survey. New elements of the methods were integrated into the developed systematic procedure, which was subsequently validated in 7 plants of the one company on the same position. The application of the developed model was verified by an expert group consisting of 7 members, an odd number, and the developed checklists and risk register were applied. On the basis of the verification, the model, checklist and risk register were corrected. In addition, the scoring method and the risk matrix were also used, but they did not contain new elements. The procedure is still in use today and employees have been trained to use it. On the basis of the developed methodology and the Checklist, the procedure has been transposed into the European OiRA tool and can be used by companies throughout the European Union.